ANALISIS FAKTOR PENYEBAB MAHASISWA UNIVERSITAS RIAU TIDAK BERPARTISIPASI PADA PILKADA SERENTAK 2015 DI PROVINSI RIAU - Asri Dewi; Sri Erlinda; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research background to the phenomenon that occurs in the student environment at the time of the elections simultaneously in 2015 that dilaksanaka in the province of Riau, which is where the students are not able to maximize participation in the restoration of Regional Head simultaneously performed by Riau Province in 2015, dikarnakan there are different obstacles. The research problems are whether the factors causing students Riau Universiats not berpartisiapsi on the elections simultaneously in 2015 in the province. The purpose of this study was to ascertain the Causes of University Students Riau Not Participate In Elections Simultaneously In Riau province, 2015. The population in this study is 27 568 people and a sample of 180 respondents, with the data collection techniques with the use of questionnaires, interviews, observation, documentation, library research and analysis technique with the formula P = F / N × 100. The results of this study are from the percentage recapitulation of the answers to the questionnaire respondents can be concluded that the most important reason is to encourage students at the University of Riau did not participate in the elections Unison 2015 in Riau Province is a political factor by reason of suspicion against the government, favorable ruling, politics is dirty, are outside the city ( distances) from TPS, and no stimulants of political discussions, regardless of the purpose of society, not alienate, no stimulants of banners, do not have identity cards of voters, not realizing that having Hamasa / electronics, not enrolled in DPT , not realizing that it has an obligation, participate only in vain, fearing negative consequences, not interested in the implementation of the election, the economy is low, a factor not have ID cardsKeywords: Students, of participation , elections Unison